Epidemiology of Feline Foamy Virus and Feline Immunodeficiency Virus Infections in Domestic and Feral Cats: a Seroepidemiological Study - Winkler, I. G. (American Society for Microbiology, 1999)
Although foamy viruses (Spumaviruses) have repeatedly been isolated from both healthy and diseased cats, cattle, and primates, the primary mode of transmission of those common viruses remains undefined. A database of the feline foamy virus (FeFV) and feline immunodeficiency virus (FIV) antibody status, age, and sex of 389 domestic cats presented to veterinarians was assembled. A similar database for 66 feral (wild) cats was also assembled. That FeFV antibody status reflects infection was validated by PCR. Both FeFV and FIV infection rates were found to gradually increase with age, and over 70% of cats older than 9 years were seropositive for FeFV. In domestic cats, the prevalence of FeFV infection was similar in both sexes. In feral cats, FeFV infection was more prevalent in female cats than in male cats. Although both FeFV and FIV have been reported to be transmitted by biting, the patterns of infection observed are more consistent with an interpretation that transmission of these two retroviruses is not the same. The prevalence of FIV infection is highest in nondesexed male cats, the animals most likely to display aggressive behavior. The gradual increase in the proportion of FeFV-infected animals is consistent with transmission of foamy viruses by intimate social contact between animals and less commonly by aggressive behavior.